A Method of Experimental Studies of Heat Transfer Processes between Adjacent Facilities - Nizhnyk, Vadym; Shchipets, Stanislav; Tarasenko, Olexandr; Kropyvnytskyi, Vitalii; Medvid, Bogdan (International Journal of Engineering and Technology, 2018)
A method of experimental studies of heat transfer processes between adjacent facilities during fire was developed. Equipment necessary for the experimental studies was determined. A new specimen type for studies was created in order to perform experimental studies. Configuration of the specimen for the studies allows simulation of a building fragment with filler structures which is affected by heat radiation emitted by fire. Points of placement of the specimens for studies relative to the heat flux source when conducting experimental studies were substantiated. It was revealed that height of the specimen installation shall be determined so that the test specimen is located below the flame tip in order to take into account the most severe impact of heat radiation coming from the fire bed and to exclude any possibility of irradiation from the ground surface. It was proposed that the test specimens are placed at the level of the lower edge of the window opening of the building fragment at the distances of2 m,4 mand6 mfrom the building fragment. The sequence of conduction of experimental studies of heat transfer processes between adjacent facilities during fire was developed.Â